The Slit–Robo signalling pathway in nervous system development: a comparative perspective from vertebrates and invertebrates - Nicole Sanhueza; Evelyn C. Avilés; Carlos Oliva (Open Biology)
During nervous system development, growing axons find their targets with the help of guidance cues. These cues, which can be secreted molecules provided by neighbouring cells or transmembrane proteins mediating cell–cell contacts with the growing axons, act as either chemoattractants or chemorepellents. Over the last decades, several axon guidance molecules have been identified. One of the classical guidance cues is the Slit protein. Slit is a secreted protein, initially identified in a genetic screen in the fruit fly Drosophila melanogaster but later shown to be present in other organisms including vertebrates. Slit was originally classified as a repellent guidance cue, but nowadays it is recognized as a promoter of axonal growth in some contexts. Slit action is mediated mainly by the Roundabout (Robo) family of single pass transmembrane proteins, although it has been shown more recently that other proteins can also function as Slit receptors. In this review, we describe the main aspects of Slit–Robo signalling during development of the nervous system. We start with a historical view of the discovery of these proteins, followed by a description of their main molecular characteristics. We then explore specific examples that describe the functions and signal transduction mechanisms of this signalling pathway.